Circular RNA CDR1as Inhibits the Metastasis of Gastric Cancer through Targeting miR-876-5p/GNG7 Axis - Jiajia Jiang; Rong Li; Junyi Wang; Jie Hou; Hui Qian; Wenrong Xu (Gastroenterology Research and Practice)
Circular RNA CDR1as has been demonstrated to participate in various cancer progressions as miRNA sponges. The exact underlying mechanisms of CDR1as on gastric cancer (GC) metastasis remain unknown. Here, we found that CDR1as knockdown facilitated GC cell migration and invasion while its overexpression inhibited the migration and invasion abilities of GC cells in vitro and in vivo. Moreover, epithelial-mesenchymal transition- (EMT-) associated proteins and MMP2 and MMP9 were downregulated by CDR1as. Bioinformatics analysis combined with dual-luciferase reporter gene assays, western blot, RT-qPCR analysis, and functional rescue experiments demonstrated that CDR1as served as a miR-876-5p sponge and upregulated the target gene GNG7 expression to suppress GC metastasis. In summary, our findings indicate that CDR1as suppresses GC metastasis through the CDR1as/miR-876-5p/GNG7 axis.